Symbolic Da'wah of Cultural Acculturation of Muhammad Cheng Hoo Mosque Purbalingga - M. Wahyu Fauzi Aziz; Musmuallim; M. Happy Nur Tsani, (International Journal of Scientific Research and Management (IJSRM), 2022)
This study examines the symbolic preaching of Chinese Islam at the Muhammad Cheng Hoo Mosque, Purbalingga Regency, Central Java. A place of worship that has become a symbol of a house of worship for Chinese Muslims in particular and Muslims in general. The architecture of the building which is unique, interesting, and similar to that of a temple as a place of worship for the Confucian people is a distinctive feature of the Islamic treasures. Cheng Hoo Purbalingga Mosque has an attraction, from the physical side, it is not so visible as a mosque building, but when you go inside, the nuances of Islam will clearly show the mixture of Chinese cultural acculturation with Islam. This study concludes that the ornaments and shapes of this mosque contain symbolic values ​​and messages (wisdom) of da’wah. The symbolic values ​​of da’wah contained, namely: the value of beauty (artistic), cultural values ​​(turats), accommodative values, brotherhood values ​​(ukhuwah) and the value of unity. The establishment of the Cheng Hoo Mosque gave a message (wisdom) of da’wah that Islam teaches hospitality and openness to all cultural entities, Islam adapts and interacts with various social traditions and Islam teaches tolerance in a life full of diversity.